The Influence of Training and Career Development on Employee Performance at PT. Indofood Cbp Sukses Makmur Tbk Bogasari Division - Lismiatun, Lismiatun; Yanuarso, Bambang Purnomo; Fauziah, Gina (Peneliti.net, 2024)
This research aims to determine the effect of Training and Career Development on Employee Performance both partially and simultaneously at PT. Indofood CBP Sukses Makmur Tbk Bogasari Division. The method used in this research is quantitative. The analysis technique uses statistical analysis by testing validity tests, reliability tests, classical assumption tests, descriptive analysis, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, coefficient of determination tests, t tests and F tests. The sample used was 67 respondents from a population of 205 people using the Slovin formula. The research results show that training and career development contribute to employee performance by 27.2% with the multiple linear regression equation Y = 16.704 + 0.275X1 + 0.289X2. The results of the simultaneous influence test showed that Fcount = 11.927 > Ftable = 3.14, so it can be concluded that there is a significant influence between training and career development on the performance of PT employees. Indofood CBP Sukses Makmur Tbk Bogasari Division